In Vitro Aberrometric Assessment of a Multifocal Intraocular Lens and Two Extended Depth of Focus IOLs - Vicente J. Camps; Angel Tolosa; David P. Piñero; Dolores de Fez; María T. Caballero; Juan J. Miret (Journal of Ophthalmology)
Purpose. To analyze the “in vitro” aberrometric pattern of a refractive IOL and two extended depth of focus IOLs. Methods. A special optical bench with a Shack-Hartmann wavefront sensor (SH) was designed for the measurement. Three presbyopia correction IOLs were analyzed: Mini WELL (MW), TECNIS Symfony ZXR00 (SYM), and Lentis Mplus X LS-313 MF30 (MP). Three different pupil sizes were used for the comparison: 3, 4, and 4.7 mm. Results. MW generated negative primary and positive secondary spherical aberrations (SA) for the apertures of 3 mm (−0.13 and +0.12 μm), 4 mm (−0.12 and +0.08 μm), and 4.7 mm (−0.11 and +0.08 μm), while the SYM only generated negative primary SA for 4 and 4.7 mm apertures (−0.12 μm and −0.20 μm, resp.). The MP induced coma and trefoil for all pupils and showed significant HOAs for apertures of 4 and 4.7 mm. Conclusions. In an optical bench, the MW induces negative primary and positive secondary SA for all pupils. The SYM aberrations seem to be pupil dependent; it does not produce negative primary SA for 3 mm but increases for higher pupils. Meanwhile, the HOAs for the MW and SYM were not significant. The MP showed in all cases the highest HOAs.